Skeletal myogenic differentiation of human urine‐derived cells as a potential source for skeletal muscle regeneration. (19th June 2014) - Chen, Wei; Xie, Minkai; Yang, Bin; Bharadwaj, Shantaram; Song, Lujie; Liu, Guihua; Yi, Shanhong; Ye, Gang; Atala, Anthony; Zhang, Yuanyuan
Abstract: Stem cells are regarded as possible cell therapy candidates for skeletal muscle regeneration. However, invasive harvesting of those cells can cause potential harvest‐site morbidity. The goal of this study was to assess whether human urine‐derived stem cells (USCs), obtained through non‐invasive procedures, can differentiate into skeletal muscle linage cells (Sk‐MCs) and potentially be used for skeletal muscle regeneration. In this study, USCs were harvested from six healthy individuals aged 25–55. Expression profiles of cell‐surface markers were assessed by flow cytometry. To optimize the myogenic differentiation medium, we selected two from four different types of myogenic differentiation media to induce the USCs. Differentiated USCs were identified with myogenic markers by gene and protein expression. USCs were implanted into the tibialis anterior muscles of nude mice for 1 month. The results showed that USCs displayed surface markers with positive staining for CD24, CD29, CD44, CD73, CD90, CD105, CD117, CD133, CD146, SSEA‐4 and STRO‐1, and negative staining for CD14, CD31, CD34 and CD45. After myogenic differentiation, a change in morphology was observed from 'rice‐grain'‐like cells to spindle‐shaped cells. The USCs expressed specific Sk‐MC transcripts and protein markers (myf5, myoD, myosin, and desmin) after being induced with different myogenic culture media. Implanted cells expressed Sk‐MC markers stably in vivo . Our findings suggest that USCs are able to differentiate into the Sk‐MC lineage in vitro and after being implanted in vivo . Thus, they might be a potential source for cell injection therapy in the use of skeletal muscle regeneration. Copyright © 2014 John Wiley & Sons, Ltd.